Risk of early horizontal transmission of hepatitis B virus in children of uninfected mothers in sub-Saharan Africa: a systematic review and meta-analysis - (:unkn) unknown (My University, 2023)
BackgroundSub-Saharan Africa is highly endemic for hepatitis B virus (HBV); historically, most people were exposed during childhood through vertical or horizontal transmission. Although all African countries now provide a three-dose infant hepatitis B vaccination starting at age 6–8 weeks, only a third of African countries have introduced birth dose (HepB-BD) vaccine. Adding HepB-BD is fundamental to prevent vertical transmission, but its effectiveness in preventing horizontal transmission, compared with the three-dose infant vaccination alone, is unknown. We aimed to estimate the risk of early horizontal transmission in children of hepatitis B surface antigen (HBsAg)-negative mothers in sub-Saharan Africa stratified according to the vaccination schedule.MethodsIn this systematic review and meta-analysis we searched MEDLINE, Global Health, Embase, African Index Medicus and African Journals Online from their inception to Oct 24, 2022, for studies reporting HBsAg or HBV DNA, or both, in children (aged 0–5 years) of HBsAg-negative mothers. We excluded studies if children were only tested at birth. Two reviewers independently screened the titles and abstracts of all articles and data were extracted using a standardised pre-piloted data extraction sheet, and authors were contacted if any important information was missing. The primary outcome was the risk of HBV infection in children of HBsAg-negative mothers, stratified by vaccination schedule (no vaccination, first dose at 6–8 weeks, or first dose at birth). We pooled the child risks of HBsAg or HBV DNA-positivity from the age of 0 years to 5 years via a random-effect meta-analysis using a generalised linear mixed model. The study was registered on PROSPERO, CRD42021236203.FindingsOf 8856 articles identified, 27 studies evaluating 10 003 children of HBsAg-negative mothers were included. The pooled risks of infection were 6·16% (95% CI 3·05–12·04; 155/1407) in the no vaccination group, 0·21% (
Keywords: African Research